Corrosions impact on wire rope strand response Comparison with a theoretical predictive model - Amal Tijani; Meryam Meknassi; Hassan Chaffoui; Mohamed Elghorba (Fracture and Structural Integrity)
In this work, we investigate the behavior of wire ropes when they are subject to corrosion damage. The method is based on accelerated corrosion using experimentation as well as a theoretical predictive model. The experimental approach used static tensile tests on corroded strands. A loss in rigidity and decrease of the ultimate force was observed. For the predictive model, the residual ultimate force was evaluated at a time t in function of the initial diameter, the residual diameter at time t and the ultimate force of the original strand. Given that the obtained residual force evolution depending on the strands fraction of life matched for both methods, the proposed predictive model can be used by engineers to assess if the wire rope needs to be changed to ensure a good maintainability of structures. Actually, when the applied force on the wire rope approaches its residual bearing force determined by a measure of the residual diameter, the wire rope removal is mandatory